Broadcasting scalable video with generalized spatial modulation in cellular networks - Correia, A. (2020)
This paper considers the transmission of scalable video via broadcast and multicast to increase spectral and energy efﬁciency in cellular networks. To address this problem, we study the use of generalized spatial modulation (GSM) combined with non-orthogonal hierarchical M-QAM modulations due to the capability to exploit the potential gains of large scale antenna systems and achieve high spectral and energy efficiencies. We introduce the basic idea of broadcasting/multicasting scalable video associated to GSM, and discuss the key limitations. Non-uniform hierarchical QAM constellations are used for broadcasting/multicasting scalable video while user specific messages are carried implicitly on the indexes of the active transmit antennas combinations. To deal with multiple video and dedicated user streams multiplexed on the same transmission, an iterative receiver with reduced complexity is described. 5G New Radio (NR) based link and system level results are presented. Two different ways of quadruplicating the number of broadcasting programs are evaluated and compared. Performance results show that the proposed GSM scheme is capable of achieving flexibility and energy efficiency gain over conventional multiple input multiple output (MIMO) schemes.